1998
DOI: 10.1038/sj.jhh.1000599
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of percutaneous angioplasty vs continued medical therapy for hypertensive patients with atheromatous renal artery stenosis

Abstract: Methods: A total of 135 eligible patients were identified, of whom 55 (44%) were randomised. Eligible patients had sustained hypertension, with a minimum diastolic BP of 95 mm Hg on at least two anti-hypertensive drugs. Renal artery stenosis was defined by renal angiography as at least 50% stenosis in the affected vessel. All patients were observed during an initial 4-week run-in period on a fixed drug regimen and subsequent changes measured from this 4-week baseline. Results: Blood pressure fell during the ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(43 citation statements)
references
References 11 publications
0
38
0
5
Order By: Relevance
“…11 However, three randomized trials of renal-artery angioplasty failed to show a benefit with respect to blood pressure. 12-14 Two subsequent randomized trials of stenting did not show a benefit with respect to kidney function. 15,16 To our knowledge, no studies to date have been designed specifically to assess clinical outcomes.…”
mentioning
confidence: 99%
“…11 However, three randomized trials of renal-artery angioplasty failed to show a benefit with respect to blood pressure. 12-14 Two subsequent randomized trials of stenting did not show a benefit with respect to kidney function. 15,16 To our knowledge, no studies to date have been designed specifically to assess clinical outcomes.…”
mentioning
confidence: 99%
“…35 It showed higher efficacy in lowering blood pressure yet no added advantage in terms of reversing or halting the progression of renal disease. 35 However, with advanced medical therapies, the role of RAAS has diminished, and it is no longer superior to medical management. 36 In addition, there is certainly no role for stenting in incidentally identified renal artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The first three studies used change in blood pressure as the primary outcome [7,8,9] and the more recent trials used renal function [10,11,12] or a composite of renal functional change, cardiovascular events and mortality [12] as the primary outcome. The neutral results of these trials have several potential explanations, but an important one is the fact that patients who were most likely to benefit from renal revascularization, namely, the high-risk patients as typified by our group 1 (progressive decline of renal function) comprised only a minority of the randomized populations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown no overall benefit from revascularization [7,8,9,10,11,12], although a recent meta-analysis has shown a significant reduction in the number of anti-hypertensives at the end of follow-up period in the revascularized cohort [13]. …”
Section: Introductionmentioning
confidence: 99%